THE IMPACT OF CLOSURE DEVICES ON VASCULAR COMPLICATIONS DURING TRANSCATHETER AORTIC VALVE IMPLANTATION PROCEDURES IN GERIATRIC PATIENTS - Ustunel, Latif; Ozguler, Ibrahim Murat (Turkish Geriatrics Soc, 2021)
Introduction: In transcatheter aortic valve implantation, some closure devices can be used as an alternative to the surgical exploration of the femoral artery for vascular access. This study aimed to compare closure devices and surgical exploration techniques in terms of vascular access complications, particularly in geriatric patients. Materials and Methods: This study included 169 patients who had undergone transcatheter aortic valve implantation at a cardiology clinic between August 2014 and January 2019. The patients' mean age was 76.62 years; 53.30% were male. The preferred access site was the femoral artery in all the patients. Patients in whom a closure device was used were included in the Prostar and ProGlide groups, and those who underwent surgical exploration of the femoral artery were included in the Surgery group. The endpoints of the study were postoperative bleeding, infection, and a recurring need for surgical repair. Results: Of the patients, 55.60%, 29.60%, and 14.80% were included in the Prostar, ProGlide, and Surgery groups, respectively. No significant differences were observed between the Prostar and ProGlide groups regarding the rate of need for emergency surgery due to bleeding. During post-procedure followups, the emergency surgery and bleeding rates were significantly higher in the Prostar and ProGlide groups than those in the Surgery group. Conclusion: Although no difference exists between the closure devices used for vascular access in terms of complications, surgical exploration reduces the rate of bleeding-related complications thereby reducing the complication risk, except for the possible occurrence of surgical site infections.
Keywords: Transcatheter Aortic Valve Replacement; Vascular Closure Device; Femoral Artery